2022
DOI: 10.1108/ijoem-08-2021-1249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of government ownership on private sector enterprises’ environmental responsibility: empirical evidence from Chinese listed firms

Abstract: Purpose Against the background of actively promoting the reform of mixed ownership in China, this study regards government ownership in private sector enterprises (PSEs) as an important political connection mechanism and examines private holding listed companies in high-polluting industries that sold China A-shares from 2012 to 2019.Design/methodology/approach Using regression models such as Tobit and negative binomial estimation, the research empirically examines the impact of government ownership in PSEs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Some studies focus on the factors that influence digital transformation. At the micro level, these factors include manager characteristics [ 30 ], organizational structure [ 22 ], dynamic capabilities [ 31 ], profit expectations [ 32 ], digital strategies [ 23 ], financial asset allocation [ 33 ], and equity structure [ 34 ]. At the macro level, these factors include digital technology [ 35 ], financial technology [ 36 ], digital infrastructure construction [ 37 ], policy guarantees [ 24 ], and the business environment [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies focus on the factors that influence digital transformation. At the micro level, these factors include manager characteristics [ 30 ], organizational structure [ 22 ], dynamic capabilities [ 31 ], profit expectations [ 32 ], digital strategies [ 23 ], financial asset allocation [ 33 ], and equity structure [ 34 ]. At the macro level, these factors include digital technology [ 35 ], financial technology [ 36 ], digital infrastructure construction [ 37 ], policy guarantees [ 24 ], and the business environment [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, political connections will promote corporate green innovation and play a role in "Resource effect" [10]; the other side believes that political connections may lead to companies abusing power or enjoying privileges, helping companies circumvent environmental systems [11], and punishing companies for environmental violations Producing a "shelter effect" [12], that is, reducing the intensity of penalties for violations, thereby relaxing the emphasis on and improvement of environmental issues. Regarding the impact of political connections on companies' performance of social responsibilities, one party believes that political connections can promote corporate charitable behaviors [13] and the fulfillment of social responsibilities [14]. The other side believes that political connections may weaken companies' consideration and response to social interests and reduce corporate social responsibility information disclosure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on the mixed ownership reform of SOEs have mainly explored around firm performance (Dong et al, 2022;Iwasaki et al, 2022), innovation (Zhang et al, 2020;Cao et al, 2020;Yang et al, 2023), risk-taking (Khaw et al, 2016;Zhang et al, 2021) and governance effectiveness (Zhang et al, 2022). Existing research studies on corporate environmental behaviour focus on environmental policies such as environmental protection laws (Fang et al, 2021;Liu et al, 2021a), environmental regulation (Huang and Lei, 2021;Cui et al, 2022), stakeholders (Yu et al, 2022) and other factors to study corporate behaviours such as green innovation (Li et al, 2023) and social responsibility (Xue et al, 2022;Bardos et al, 2020). Relevant studies have concluded that with the continuous entry of non-state capital and continuous decline of state-owned shareholding ratio, business objectives have been purified to a certain extent and the policy obligations undertaken by enterprises have been significantly reduced (Zhang et al, 2022;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%